2008
DOI: 10.1038/nmat2334
|View full text |Cite
|
Sign up to set email alerts
|

Determination of spin injection and transport in a ferromagnet/organic semiconductor heterojunction by two-photon photoemission

Abstract: A fundamental prerequisite for the implementation of organic semiconductors (OSCs) in spintronics devices is the still missing basic knowledge about spin injection and transport in OSCs. Here, we consider a model system consisting of a high-quality interface between the ferromagnet cobalt and the OSC copper phthalocyanine (CuPc). We focus on interfacial effects on spin injection and on the spin transport properties of CuPc. Using spin-resolved two-photon photoemission, we have measured directly and in situ the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
224
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(235 citation statements)
references
References 14 publications
6
224
1
1
Order By: Relevance
“…This study has shown that the microstructure in organic spin valve devices is closely correlated with magnetotransport, in agreement with the literature 44 . On the basis of an optimized evaporation temperature for the C 60 layer at 723 K, we deduced that an efficient SDT pathway exists in a spin valve device with a C 60 layer of 80 nm for achieving a high MR ratio in which spin electrons are efficiently injected 17,45 into the C 60 layer and hopping transport occurs with very a small spin flip, as illustrated in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has shown that the microstructure in organic spin valve devices is closely correlated with magnetotransport, in agreement with the literature 44 . On the basis of an optimized evaporation temperature for the C 60 layer at 723 K, we deduced that an efficient SDT pathway exists in a spin valve device with a C 60 layer of 80 nm for achieving a high MR ratio in which spin electrons are efficiently injected 17,45 into the C 60 layer and hopping transport occurs with very a small spin flip, as illustrated in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…The observation of SDT in OSs in the hopping process has also been reported 2,3 in such materials as tris (8-hydroxyquinolinato) aluminium (Alq 3 ) and rubrene. However, most studies have only been carried out at low temperatures because of the evident reduction in the SDT length with increasing measurement temperatures until the MR effect finally disappears at room temperature 2,[13][14][15][16][17][18][19] . Thus, whether a large SDT length can be realized in OSs at room temperature remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A main reason for the growing interest in transition metal phthalocyanines (TMPc) is their possible application in optoelectronic devices such as organic field effect transistors (OFETs), [1][2][3] organic light emitting devices (OLEDs), [4][5][6] organic photovoltaics (OPV), 4,7 and spintronic devices. [8][9][10] Increasing experimental and theoretical research efforts are devoted to the understanding of the electronic structure of this class of materials and in particular to related interfaces. [11][12][13] The performance of devices based on these materials highly depends on the behavior of the organic molecules at the interfaces with metals.…”
mentioning
confidence: 99%
“…Crystalline CuPc is a semiconducting blue dye which, in pure thinfilm form and more exotic derivatives, is currently attracting intense experimental and theoretical interest due to its potential for use as a flexible organometallic photovoltaic material 48 , as part of field-effect transistors 49 and, due to its magnetic functionality, in spintronic data storage or processing devices 50 . In this system, two correlated subspaces delineated by copper 3d-like states are spatially well separated, with approximately 3.77Å between centres, and there is minimal electronic bonding between the localized orbitals in the open Cu-3d shells in the two approximately planar moeities.…”
Section: Copper Phthalocyanine Dimermentioning
confidence: 99%